A Placebo‐Controlled, Prospective, Randomized Clinical Trial of Polyethylene Glycol and Methylprednisolone Sodium Succinate in Dogs with Intervertebral Disk Herniation. (31st October 2015) - Olby, N.J.; Muguet‐Chanoit, A.C.; Lim, J.‐H.; Davidian, M.; Mariani, C.L.; Freeman, A.C.; Platt, S.R.; Humphrey, J.; Kent, M.; Giovanella, C.; Longshore, R.; Early, P.J.; et al.
Abstract : Background: Acute intervertebral disk herniation (IVDH) is a common cause of spinal cord injury in dogs and currently there is no proven medical treatment to counter secondary injury effects. Use of methylprednisolone sodium succinate (MPSS) or polyethylene glycol (PEG) as neuroprotectants is advocated but controversial because neither treatment has been tested in placebo‐controlled, randomized, blinded trials in dogs. Hypothesis: Polyethylene glycol will improve the outcome of severe spinal cord injury caused by IVDH compared to MPSS or placebo. Animals: Client‐owned dogs with acute onset of thoracolumbar IVDH causing paralysis and loss of nociception for <24 hours. Methods: Dogs were randomized to receive MPSS, PEG, or placebo; drugs appeared identical and group allocation was masked. Drug administration was initiated once the diagnosis of IVDH was confirmed and all dogs underwent hemilaminectomy. Neurologic function was assessed 2, 4, 8, and 12 weeks postoperatively using an open field gait score (OFS) as the primary outcome measure. Outcomes were compared by the Wilcoxon rank sum test. Results: Sixty‐three dogs were recruited and 47.6% recovered ambulation. 17.5% developed progressive myelomalacia but there was no association with group. There was no difference in OFS among groups. Although full study power was not reached, conditional power analyses indicated the futility of continued case recruitment. Conclusions: This clinical trial did not show a benefit of either MPSS or PEG in the treatment of acute, severe thoracolumbar IVDH when used as adjunctive medical treatment administered to dogs presenting within 24 hours of onset of paralysis.